Republic of Korea : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
This 2013 Article IV Consultation highlights that the Republic of Korea has experienced impressive growth since the 1970s, enabling it to escape the middle-income trap. Policies should aim to tackle the weakness of domestic demand and counter forthcoming headwinds to potential growth. Korea is reaping the benefits of prudent macroeconomic management and financial moderation. The economy faces significant medium-term growth and inclusiveness challenges. Slow household income growth hinders stabilization in household debt and weighs on domestic demand, while services sector productivity is very low.